Comprehensive dental care for Autism Spectrum Disorder (ASD) patient - Anna Németh; Judit Borbély; Péter Hermann (Hungarian Dental Association, 2023)
Today's modern digital dentistry aims at predictable outcomes, made possible by facially driven treatment planning, prototype fabrication, copy-paste and continuous digital quality control. Furthermore, due to the comprehensive nature of dentistry, a satisfactory end result is obtained by considering functional, aesthetic, gnathological and periodontal aspects. In this case, we present the prosthodontic rehabilitation of a patient with Autism Spectrum Disorder (ASD), using bite-elevation and fabrication of monolithic zirconia and porcelain-fused-to-metal bridges using a combination of conventional and digital workflows. The patient is a 41-year-old female with ASD and severe mental retardation. Dysgnathia, malocclusion and deep overbite were observed. Following professional oral hygiene treatment and restorative dental procedures, a two-dimensional digital smile design (3Shape Smile Design, Copenhagen, Denmark) and digital wax-up were prepared. The virtual designs were 3D printed (NextDent, 3D Systems, Rock Hill, USA) and used to create self-curing acrylic (Structur 2 SC A2, VOCO) mock-ups. The gothic arch tracing method was used to determine the centric relation position and a digital jaw movement analysis was performed with a digital facebow (Zebris for Cermaill, Aman Girrbach, Austria). Based on the increased occlusal vertical dimension long-term temporary polymethyl methacrylate restorations were fabricated. After 3 months of provisional period the functional temporary prostheses were copied with a copy-paste technique using an intraoral scanner (3Shape Trios 3 Pod, Copenhagen, Denmark) to provide the design of the final prostheses. In this case, we made a lower and upper pre-preparation scan and registered the intercuspidal position. In the next step, upper and lower digital precision-situational impressions were taken. The pre-prep and prep scans were aligned in 3Shape design software (3Shape Design Studio), where the final restorations were then designed. To record and mount the proper maxillo-mandibular relationship of the casts, a silicon bite registration was used before the veneering process of the lower metal frameworks The final restorations were cemented with resin-modified glass ionomer cement (GC Fuji Plus, GC Corp., Tokyo, Japan). If the steps of the modern digital workflow are carefully followed, necessarily supplemented by analogue steps, a predictable end result is achieved that is both functionally and aesthetically satisfying the patient.